2001
DOI: 10.2307/1592883
|View full text |Cite
|
Sign up to set email alerts
|

The Spread of Salmonella gallinarum 9R Vaccine Strain under Field Conditions

Abstract: A live vaccine based on an attenuated Salmonella gallinarum 9R strain is in use in a Salmonella enteritidis control program in commercial layer flocks in The Netherlands. In a field study, the potential spread of the vaccine strain from vaccinated flocks to nonvaccinated flocks has been studied after both the primary and the booster injection at four different rearing farms and at one layer farm. The vaccinated and the nonvaccinated flocks were monitored at regular intervals by bacteriologic and serologic exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…5 %) [27]. In 4500 eggs derived from five S. Gallinarum 9R vaccinated flocks, no vaccine strain bacteria were detected, while no evidence was found in another study for the faecal spread of the vaccine strain [26,100].…”
Section: Vaccines and Adaptive Immunitymentioning
confidence: 84%
“…5 %) [27]. In 4500 eggs derived from five S. Gallinarum 9R vaccinated flocks, no vaccine strain bacteria were detected, while no evidence was found in another study for the faecal spread of the vaccine strain [26,100].…”
Section: Vaccines and Adaptive Immunitymentioning
confidence: 84%
“…This theory was confirmed in a large field trial in the Netherlands in which 80 commercial flocks were vaccinated with the SG9R vaccine strain and the flock level of occurrence of SE infections was 2.5% (2/80 flocks), which was significantly less than that in unvaccinated flocks (214 out of 1854 flocks, 11.5%; Feberwee et al, 2001a). No vaccine strain bacteria were detected in 4500 eggs derived from five SG9R vaccinated flocks, while in another study no evidence was found for the faecal spread of the vaccine strain (Feberwee et al, 2000(Feberwee et al, , 2001b.…”
Section: Discussionmentioning
confidence: 87%
“…The infections by SG are usually acute, and the spread of the bacteria is more intense if carcasses of infected dead chickens are exposed to other chickens (BARROW et al, 1994;BERCHIERI JR. et al, 2000). SG can survive in the animal environment, and, due to the constant and slow horizontal transmission, the mortality is persistent in affected flocks, making it difficult to eradicate the infection (FEBERWEE et al, 2001b).…”
Section: Palavras-chavementioning
confidence: 99%